Change in Transverse Slope of Water Surface at River Bend: A Numerical Study - Rahman, Priyata; Ali, Md Shahjahan (Journal of Engineering Science, 2021)
Generation of secondary current in a meandering river flow due to the centrifugal force acting on the bend is three dimensional (3D) in nature. But in case of practical problems like alluvial geomorphic processes, 3D models are not proved to be efficient. Hence, two dimensional (2D) models are generally adopted for such problems. This study offers a presentation of numerical simulation results for turbulent flows around bends of a meandering channel for different meander angles. 2D models were built by the use of iRIC Nays2DH solver for flow simulation of 45˚, 90˚, 135˚, 180˚ meandering bends with varying widths of 0.15m, 0.25m, 0.75m, 1.00m, 1.25m and 1.50m considering constant Froude number with constant meandering length (ML/W) and constant radius of curvature (R/W). Zero equation model was used as turbulence closure with finite differential advections as upwind scheme. The flow behavior has been studied at the apex and cross over portions of bends. From the simulation, the velocity at outer bank was found to be lower than that of the inner bank while the water surface elevation was found to be higher than that of the inner bank. Increase in transverse slope of water surface at bend was observed for increasing meander angles, Froude numbers and decreasing channel widths. Journal of Engineering Science 12(2), 2021, 93-101